Predictors of family screen time exposure among students in selected higher education institutions in central Luzon, Philippines - Albino, Michael G.; Albino, Femia S.; Costales, Jefferson A.; Asio, John Mark R.; Riego de Dios, Erin E.; De Guzman, Marie Fe D. (Humanities, Arts and Social Sciences Studies, 2023)
This study aims to determine the predictors of family screen time exposure among higher education students in Central Luzon, Philippines. This study used a descriptive correlation research design with the help of an online survey as the primary data-gathering tool. With the help of convenience sampling, 290 students voluntarily participated in the online survey. The proponents used a modified questionnaire which underwent validity and reliability (Cronbach Alpha = 0.90). For data analysis, the study used descriptive and inferential statistics with the help of SPSS 23. The study found that attitude (x̅ = 2.88), expectation (x̅ = 2.76), and family support (x̅ = 2.85) got an “often” remarks from the respondents and only family opinion (x̅ = 2.37) got a “sometimes” response. The available gadgets or devices of the respondents is one (x̅ = 1.78) and they “often” observe family as model of screen time exposure (x̅ = 2.73). Inferential statistics further confirmed the association between expectation (r = .336), opinion (r = .202), support (r = .167), the presence of gadgets (r = .265) with family as a model. Finally, the respondents’ opinion (B = .451), support (B = .423), and the presence of gadgets and devices (B = .181) predicted the family as a model for screen time exposure. The researchers recommend important suggestions to students, family, faculty, and the institution in dealing with screen time exposure management.